The soundscape of Arctic Charr spawning grounds in lotic and lentic environments: can passive acoustic monitoring be used to detect spawning activities?. Issue 1 (2nd January 2018) - Bolgan, Marta; O'Brien, Joanne; Chorazyczewska, Emilia; Winfield, Ian J.; McCullough, Peter; Gammell, Martin
Abstract: The aims of this study were to (i) assess the efficacy of passive acoustic monitoring (PAM) for detecting Arctic Charr at their spawning grounds and (ii) characterize the overall acoustic soundscape of these sites. PAM was carried out over three Arctic Charr spawning grounds in the UK, one lotic and two lentic. 24-h cycles of recordings were collected prior to and during the Arctic Charr spawning season, which was determined from data returns by simultaneous net monitoring. Acoustic analysis consisted of manual quantification of sound sources, Acoustic Complexity Index (ACI) calculation and spectral analysis in 1/3 octave band (SPL; dB re 1 μPa). In the lotic spawning ground, prior to the beginning of Arctic Charr spawning, SPL and ACI showed a restricted range of variation throughout the 24-h, while during spawning the night values of SPL and ACI were found to significantly increase, concurrently with the rate of gravel noise induced by fish spawning activities and fish air passage sounds. Both prior to and during the Arctic Charr run, the lentic soundscape was characterized by diel variation due to the daytime presence of anthropogenic noise and the night-time presence of insect calls, while only a few occurrences of fish air passage sounds and gravel noise were recorded. These findings suggest that PAM over Arctic Charr spawning grounds could provide meaningful information to be used in developing management plans for this threatened species, such as determining the location and time of arrival, diel pattern and length of spawning activities.